A Review of ApoE4 Interference Targeting Mitophagy Molecular Pathways for Alzheimer's Disease - Chen, Huiyi; Chen, Feng; Jiang, Ying; Zhang, Lu; Hu, Guizhen; Sun, Furong; Zhang, Miaoping; Ji, Yao; Chen, Yanting; Che, Gang; Zhou, Xu; Zhang, Yu (Frontiers in Aging Neuroscience, 2022)
Alzheimer’s disease (AD) is one of the major worldwide causes of dementia that characterized 17 by irreversable learning decline, memory loss and behavior impairments. Mitophagy is a selective 18 autophagy through clearance of aberrant mitochondria for specifically degradation to maintain energy 19 generation, neuronal and synaptic function in brain. Accumulating evidence shows defective 20 mitophagy is believed as one of the early and prominent features in AD pathogenesis and draws 21 attention in recent years. APOE ε4 allele is the greatest genetic determinant for AD and is widely 22 reported to mediates detrimental effects on mitochondria function and mitophagic process. Given the 23 continuity of physiological process, this review takes mitochondrial dynamic and mitophagic core 24 events into consideration, highlights current knowledge about the molecular alterations from an 25 APOE-genotype perspective, synthesizes ApoE4-associated regulations and the cross talk between 26 these signaling, along with the focuses on general autophagic process and several pivotal processes of 27 mitophagy, including mitochondrial dynamic (DRP1, MFN-1), mitophagic induction (PINK1, 28 Parkin). These may shed new light on the link between ApoE4 and AD and provide novel insights for 29 promising mitophagy-targeted therapeutic strategies for AD.